Nucleus segmentation technique for acute leukemia - Nurul Hazwani, Abd. Halim; Mohd Yusof, Mashor, Prof. Dr.; A. S., Abdul Nasir; N. R., Mokhtar; H., Rosline (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/